Cool episode and platform demise in the Early Aptian: New insights on the links between climate and carbonate production. (16th January 2016) - Bonin, Aurélie; Pucéat, Emmanuelle; Vennin, Emmanuelle; Mattioli, Emanuela; Aurell, Marcos; Joachimski, Michael; Barbarin, Nicolas; Laffont, Rémi
Abstract: The Early Aptian encountered several crises in neritic and pelagic carbonate production, major perturbations in the carbon cycle, and an oceanic anoxic event (OAE1a). Yet the causal links between these perturbations and climate changes remain poorly understood, partly because temperature records spanning the Early Aptian interval are still scant. We present new δ 18 O data from well‐preserved bivalves from a carbonate platform of the Galve subbasin (Spain) that document a major cooling event postdating most of OAE1a. Our data show that cooling postdates the global platform demise and cannot have triggered this event that occurred during the warmest interval. The warmest temperatures coincide with the time equivalent of OAE1a and with platform biotic assemblages dominated by microbialites at Aliaga as well as on other Tethyan platforms. Coral‐dominated assemblages then replace microbialites during the subsequent cooling. Nannoconids are absent during most of the time equivalent of the OAE1a, probably related to the well‐known crisis affecting this group. Yet they present a transient recovery in the upper part of this interval with an increase in both size and abundance during the cool interval portion that postdates OAE1a. An evolution toward cooler and drier climatic conditions may have induced the regional change from microbial to coral assemblages as well as nannoconids size and abundance increase by limiting continent‐derived input of nutrients. Key Points: Cooling evidenced during the late Early Aptian, postdating most of OAE1a Warmest interval coincides with OAE1a and microbialites development Change in neritic carbonate assemblages and in nannoconid size during cooling